Does crop succession and nitrogen splitting fertilization change the technological quality of common bean? - Mingotte, Fábio Luiz Checchio [UNESP]; Jardim, Celso Antônio [UNESP]; Coelho, Anderson Prates [UNESP]; Yada, Marcela Midori [UNESP]; Leal, Fábio Tiraboschi [UNESP]; Lemos, Leandro Borges [UNESP]; Filho, Domingos Fornasieri [UNESP] (FapUNIFESP (SciELO), 2021)
The crop succession and nitrogen splitting fertilization are managements that can affect the common bean technological quality and, consequently, the profitability of producer and the food biological value. The aim of this study was to evaluate whether crop succession and N splitting fertilization promote differences in the technological quality of common bean grains. The experiment was carried out during winter over two agricultural years in southeastern Brazil. A randomized block design was used in a split-plot scheme, with four replications. The plots were composed of three crop successional systems (maize sole, maize + Urochloa ruziziensis, U. ruziziensis sole) and the subplots contained nine combinations of N splitting fertilization at a rate of 90 kg·ha-1 N top-dressing in the phenological stages V3, V4, and R5 of the common bean and a control without fertilization. The evaluated variables were: sieve yield greater than or equal to 12 (SY ≥ 12), crude protein content, cooking time, and hydration ratio. Crop succession promotes differences in the technological quality of common bean; however, the N splitting fertilization did not change the technological attributes of grains. The highest technological quality of common bean was obtained after succession with U. ruziziensis sole, generating large size and crude protein content of grain, followed by the succession with maize + U. ruziziensis intercropping, and finally, the succession with maize sole. Therefore, the crop succession is a fundamental factor for obtaining common bean with higher technological quality, affecting the food biological value and the profitability of producers.
Keywords: Cooking time; Crude protein content; Intercropping; Phaseolus vulgaris L.; Sieve yield